Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31486/toj.22.0003
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection With Systemic Lupus Erythematosus

Abstract: Background: Spontaneous coronary artery dissection (SCAD) has been reported to be a rare cause of acute coronary syndrome and sudden cardiac death. The clinical presentation of SCAD varies from asymptomatic to sudden death. Pregnancy is associated with SCAD, and autoimmune diseases, especially systemic lupus erythematosus (SLE), may play an important role in SCAD etiology. Case Report: A 37-year-old female with hypertension, SLE, a history of preeclampsia with 3 cesarean deliveries, and an active smoking habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…However, there are few reports on the prevalence of SCAD caused by SLE (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Chest pain was the most common symptom and was the first manifestation in two of the aforementioned cases (21,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports on the prevalence of SCAD caused by SLE (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Chest pain was the most common symptom and was the first manifestation in two of the aforementioned cases (21,25).…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous coronary artery dissection (SCAD) is another uncommon cardiac SLE manifestation, with few case reports in the literature so far. A case report by Chaaban and Kshatriya described a case of SCAD in a 37-year-old female with hypertension, and a history of smoking, both risk factors for the disease [ 47 ]. Ullah et al systematically reviewed 10 articles about SCAD associated with rheumatologic conditions and found that many cases were related to systemic lupus.…”
Section: Reviewmentioning
confidence: 99%
“…4 Vasculitis has also been associated with spontaneous coronary artery dissections in systemic lupus erythematosus (SLE). 5 Vascular intima disruption has been linked to hemodynamic and hormonal changes during pregnancy and the postpartum period, which explains the preponderance of spontaneous arterial dissection in pregnant women. 6 In our patient, the former hypothesis seemed more likely.…”
Section: Nonthrombotic Spontaneous Dissection Of Arteries Has Been Re...mentioning
confidence: 99%